The use of markets in housing policy: a comparative analysis of housing subsidy programs. Issue 1 (2nd January 2021) - Colburn, Gregg
Abstract: Many countries use demand-side housing subsidies to support low-income households. Unlike public or social housing programs, demand-side subsidies require recipients to enter the private market to use their benefits. The focus of this study is the experiences of assisted households in the private housing market and the outcomes they achieve. Given the link between policy design and program outcomes and because all housing subsidy programs are not created equal, one might expect the experiences and outcomes of recipients to also vary. To examine this relationship, using data from national housing surveys, this study analyzes cross-national variation in housing support programs and compares the housing and neighbourhood outcomes of subsidized households in the US, the UK, and the Netherlands. The findings of this study highlight that market context and policy design are associated with housing outcomes. In particular, the strong tenant supports and favourable design of housing assistance in the Netherlands is associated with favourable outcomes for subsidized households. In the US and the UK, subsidized households, in general, underperform their unsubsidized peers. This article underscores the importance of institutional context and program design when public assistance programs require recipients to enter the private market to use a benefit.